The Future of Exercise-Based Cardiac Rehabilitation for Patients With Heart Failure - Passantino, Andrea; Dalla Vecchia, Laura Adelaide; Corrà, Ugo; Scalvini, Simonetta; Pistono, Massimo; Bussotti, Maurizio; Gambarin, Fabiana Isabella; Scrutinio, Domenico; La Rovere, Maria Teresa (Frontiers in Cardiovascular Medicine, 2021)
Cardiac rehabilitation is comprehensive program that includes exercise training, cardiac risk factor modification and psychosocial assessment. Exercise training and other components of cardiac rehabilitation are safe and beneficial and result in significant improvements in quality of life, functional capacity, and heart failure-related hospitalizations. Exercise should be prescribed according to a personalized approach, by optimization and tailoring the rehabilitative program to the patient’ characteristics. Telemedicine for patients with heart failure may increase participation and overcome some of the barriers that limit CR utilisation. Specific CR programs are dedicated to patients with HF and preserved ejection fraction, older and frail patients, recipients of cardiac implantable electronic devices or left ventricular assistance device. To date, CR is a recommended treatment and should be included in the management plan of all patients with HF.